Reformed theology for the 21st century: confessional, contextual and ecumenical - S. A. Strauss (Acta Theologica)
This article scrutinises two important, recently published books on the identity of Reformed theology. These books serve as a springboard for the formation of ideas concerning the way in which Reformed theology should be practised in the 21st century. The article tests the hypothesis that the correct connection and relationship between confession, context and ecumenicity guarantees the practising of meaningful, thorough and useful Reformed theology.